Intracellular and Extracellular Antifreeze Protein Significantly Improves Mammalian Cell Cryopreservation - Jonathan A. Sreter; Thomas L. Foxall; Krisztina Varga (Biomolecules, 2022)
Cell cryopreservation is an essential part of the biotechnology, food, and health care industries. There is a need to develop more effective, less toxic cryoprotective agents (CPAs) and methods, especially for mammalian cells. We investigated the impact of an insect antifreeze protein from Anatolica polita (ApAFP752) on mammalian cell cryopreservation using the human embryonic kidney cell line HEK 293T. An enhanced green fluorescent protein (EGFP)-tagged antifreeze protein, EGFP–ApAFP752, was transfected into the cells and the GFP was used to determine the efficiency of transfection. AFP was assessed for its cryoprotective effects intra- and extracellularly and both simultaneously at different concentrations with and without dimethyl sulfoxide (DMSO) at different concentrations. Comparisons were made to DMSO or medium alone. Cells were cryopreserved at −196 °C for ≥4 weeks. Upon thawing, cellular viability was determined using trypan blue, cellular damage was assessed by lactate dehydrogenase (LDH) assay, and cellular metabolism was measured using a metabolic activity assay (MTS). The use of this AFP significantly improved cryopreserved cell survival when used with DMSO intracellularly. Extracellular AFP also significantly improved cell survival when included in the DMSO freezing medium. Intra- and extracellular AFP used together demonstrated the most significantly increased cryoprotection compared to DMSO alone. These findings present a potential method to improve the viability of cryopreserved mammalian cells.